Simulated Corn Earworm, Helicoverpa zea, Injury in an Indeterminate Soybean Cultivar at Various Growth Stages under Non-Irrigated Conditions in the Southern United States - Mariane Coelho; Donald R. Cook; Angus L. Catchot; Jeff Gore; André L. Lourenção; Edson L. L. Baldin (Agronomy, 2020)
Soybean is considered one of the most valuable crops in the United States of America. Helicoverpa zea (Boddie) is among several insect pests which are associated with soybean, damaging leaves when infestations occur during the vegetative stages, and flowers and pods during the reproductive stages, which can directly impact yield. Artificial fruit removal is a method used to understand insect damage and to adjust action levels for control. The objective of this work was to evaluate the impact of five levels of fruit removal (0%, 25%, 50%, 75% and 100%) at four stages (R2, R3, R4 and R5) on maturity and yield of soybean. These methods were used to simulate H. zea damage under controlled conditions in non-irrigated environments, during 2016 and 2017. There was a significant interaction between fruit removal timing and fruit removal level for the percentage of non-senesced main stems and abscised leaves. For soybean yield, there was no significant interaction between fruit removal timing and fruit removal level. Plots that received fruit removal treatments at R5 had significantly lower soybean yields compared to plots that received damage at other growth stages and the nontreated control. Plots with 100% fruit removal had significantly lower yields compared to plots that received any of the other fruit removal treatments. These data demonstrate that indeterminate midmaturity group IV soybeans that are commonly grown in the midsouthern region of the United States may be able to compensate for even severe levels of fruit loss early during the reproductive portion of the growing season if favorable growing conditions occur.